Immigrant Earnings Assimilation in the United States: A Panel Analysis - Rho, Deborah; Sanders, Seth (Journal of Labor Economics, 2021)
We construct the first long-term comparison of cross-sectional and panel estimates of immigrant earnings assimilation in the United States from a single data source. Unlike previous results, we find that selective out-migration of higher-earning immigrants biases downward cross-sectional estimates for all education groups. Cross-sectional estimates dramatically understate earnings growth for high-skilled foreign-born workers. The bias stems from both selective out-migration and selective employment; among high-skilled immigrants, low earners find employment with a substantial delay, while high earners work immediately on arrival. We present suggestive evidence that the H-1B visa program may play a role in estimated immigrant earnings dynamics.